2011
DOI: 10.2139/ssrn.1845542
|View full text |Cite
|
Sign up to set email alerts
|

Race, Power, and the Subprime/Foreclosure Crisis: A Mesoanalysis

Abstract: Economists' principal explanations of the subprime crisis differ from those developed by noneconomists in that the latter see it as rooted in the US legacy of racial/ethnic inequality, and especially in racial residential segregation, whereas the former ignore race. This paper traces this disjuncture to two sources. What is missing in the social science view is any attention to the market mechanisms involved in subprime lending; and economists, on their side, have drawn too tight a boundary for "the economic,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…Finally, an interdisciplinary economic-social science study of the emergence of the subprime crisis can be found in Dymski et al . (2011).…”
Section: Observational Studies Iii: Credit and Consumer Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an interdisciplinary economic-social science study of the emergence of the subprime crisis can be found in Dymski et al . (2011).…”
Section: Observational Studies Iii: Credit and Consumer Marketsmentioning
confidence: 99%
“…They adopt a two-stage OLS regression model on data obtained from RealtyTrac, the largest provider of foreclosure listings in the United States. Finally, an interdisciplinary economic-social science study of the emergence of the subprime crisis can be found in Dymski et al (2011).…”
Section: Annotated Bibliographymentioning
confidence: 99%
“…Hipotecas com taxas excessivas, multas elevadas e altas taxas de juros foram vendidas às famílias poderiam ser oferecidos empréstimos que excediam em 80% o preço das residências, ou mesmo dois novos empréstimosum para arcar com os 80% do valor da residência e outro para dar conta dos 20% restantes. Segundo Dymski (2010a), essa modalidade de empréstimo hipotecário se tornou dominante a partir de 2003, a ponto de o termo "empréstimo subprime" ser usado especificamente para se referir aos empréstimos para compra de residências feito por famílias incapazes de absorver o esquema de pagamento denominado "plain vanilla"ou seja, por um esquema regular antes utilizado pelo mercado, onde o comprador teria que ter uma poupança prévia de 20% do valor da residência para compor o empréstimo e ainda teria que usar mais de 30% de sua renda para pagamento da hipoteca Dymski (2010a). prossegue afirmando que essa dinâmica levou à explosão de preços do mercado de residências dos EUA e ao insustentável alargamento dos limites de liquidez no mercado financeiro.…”
unclassified